Integration of Local Potential in Science Learning to Improve 21st-Century Skills - Afkarina Izzata Dini , Naffa; Febri Setiya Rini , Endah (Universitas Islam Indonesia, 2024)
Science learning that integrates local culture and wisdom is an important approach that is to continue to be developed in the current educational context. Along with the growing need for qualified and competitive human resources, adjustments in learning are crucial to prepare students with 21st-century skills. This research aims to evaluate how integrating local potential in science learning to improve 21st-century skills. The method used in this study is a Systematic Literature Review (SLR), with an analysis of 13 articles selected based on relevant research criteria and focus. The study results show that using learning media based on local potentials such as cultural traditions and natural resources has an important role in improving 21st-century skills, especially critical thinking and problem-solving skills. These findings underscore the importance of integrating local potential in science curricula to facilitate the development of essential skills in the modern era.